2011
DOI: 10.1007/s10964-011-9724-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Empowerment in Youth Development: A Study of Sociopolitical Control as Mediator of Ecological Systems’ Influence on Developmental Outcomes

Abstract: Empowerment has become an influential concept and theoretical framework for social policy and practice. Still, relatively little is known about the roles that empowerment plays in the ecology of human development, particularly among young people. This article reports results of a study of psychological empowerment among young people, using data from 629 high school students (65.8% female; 96.5% non-white). Using a path analysis, we examined the role of perceived sociopolitical control--an indicator of the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
190
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(206 citation statements)
references
References 102 publications
13
190
1
2
Order By: Relevance
“…Critical consciousness and empowerment are two of the most prominent conceptual frameworks for understanding civic development and engagement among youth involved in change efforts. Research has found that civic engagement and sociopolitical control are positively related to developmental outcomes such as social capital and social trust (Flanagan et al 2015;Wray-Lake and Flanagan 2012), and negatively related to risk behaviors and psychological symptoms (Christens and Peterson 2012;Denault and Poulin 2009;Zimmerman et al 1999). These findings demonstrate that civic behaviors and the perception that one is capable of making a difference are important indicators of positive youth development.…”
Section: Resultsmentioning
confidence: 99%
“…Critical consciousness and empowerment are two of the most prominent conceptual frameworks for understanding civic development and engagement among youth involved in change efforts. Research has found that civic engagement and sociopolitical control are positively related to developmental outcomes such as social capital and social trust (Flanagan et al 2015;Wray-Lake and Flanagan 2012), and negatively related to risk behaviors and psychological symptoms (Christens and Peterson 2012;Denault and Poulin 2009;Zimmerman et al 1999). These findings demonstrate that civic behaviors and the perception that one is capable of making a difference are important indicators of positive youth development.…”
Section: Resultsmentioning
confidence: 99%
“…The 2013 winner is Christens, for his article entitled ''The Role of Empowerment in Youth Development: A Study of Sociopolitical Control as Mediator of Ecological Systems' Influence on Developmental Outcomes'' (Christens and Peterson 2012). Given that the journal publishes 12 issues per year, each containing about 11-12 manuscripts, the editors view the award as a considerably distinctive accomplishment, one exemplifying the journal's distinguished history of supporting emerging scholars (see Levesque 2011Levesque , 2012.…”
mentioning
confidence: 99%
“…Lastly, Christens and Peterson (2012) examined psychological empowerment among 629 high school students (65.8 % female; 96.5 % non-white). They examined the role of perceived sociopolitical control-an indicator of the intrapersonal component of psychological empowermentas a mediator between ecological support systems and developmental outcomes.…”
mentioning
confidence: 99%
“…The empowerment of communities have been described in various ways; empowerment is a process through which people build their capacities and competencies, both as individuals or as participating members of different groups, communities and societies, to gain or achieve results for themselves (Christens et al, 2011). The process of empowerment enables or empowers the individual or groups to take part in decisionmaking, enhance capacity, and increase ability to make changes individually and collectively (Christens & Peterson, 2012). Pretto and Pavesi (2012) also argued regarding empowerment as it is a social action process through which individuals, organizations and communities gain control over their lives and also try to improve their equity and quality of life by changing their political and social environment.…”
Section: Introductionmentioning
confidence: 99%